Dietary Intake, Nutritional Status and Academic Achievements of School Children: A study Protocol - Adhikari, Bishnu Kumar; Giri, Surendra; Upreti, Yadu Ram (Educational Journal, 2026)
Dietary intake and nutritional status of children have a big impact on their academic performance and cognitive development. This protocol of the study aims to examine the association among dietary intake, nutritional status, and academic achievement of vegetarian and non-vegetarian school children with reference to Social Cognitive Theory (SCT) and the Health Belief Model (HBM). A school based cross-sectional study is conducted among 422 children aged 6-14 years. Proportionate stratified random sampling technique is employed to ensure representativeness in vegetarian and non-vegetarian school children. Dietary intake patterns are assessed using pre-tested structured interview schedule incorporating 24hour dietary recall (24HDR) and a validated food frequency questionnaire (FFQ). Nutritional status is determined using WHO anthropometric standards. Academic achievement is obtained from school record. Statistical analysis determines association between variables through SPSS software. Collected data are analyzed and interpreted using bivariate (chi-square, t-test, Pearson r) and multivariate (multinomial logistic regression) levels. Therefore, this protocol provides the insights into the overall linkage of foods, nutrients and academic success. This study is crucial to describe the explanatory power of SCT and HBM constructs. The  data can then be used to make school nutrition policy, health education curriculum, teacher and parent engagement, school level peer dynamics and related studies.